THE INFLUENCE OF DIGITAL TRANSFORMATION, DIGITAL FINANCIAL INCLUSION, AND FINANCIAL LITERACY ON THE PERFORMANCE OF MSME ACTORS WITH DISABILITIES IN JABODETABEK - Krisnandika, Verina Ruth; Zulkarnain (Count : Journal of Accounting, Business and Management, 2025)
MSMEs serve as the backbone of the economy in Indonesia. As a result of the COVID-19 pandemic in 2020, many of the MSME sectors began to digitalise, but these MSMEs have various obstacles that have an impact on the growth of MSME performance when transforming to digitalisation, especially financial management constraints. This study was conducted to empirically prove the effect of digital transformation, digital financial inclusion, and financial literacy on the performance of MSME actors with disabilities. This study uses an associative quantitative approach with a sample size of 30 MSME actors with disabilities. The sampling technique used in this study was simple random sampling technique. The instrument used was a questionnaire. The analytical tool used was SPSS version 25. The results of this study are (1) digital transformation has no effect on the performance of MSME actors with disabilities; (2) digital financial inclusion has an effect on the performance of MSME actors with disabilities; and (3) financial literacy has no effect on the performance of MSME actors with disabilities. The limitations in this study are the research variables to examine the effect on the performance of MSME actors with disabilities, namely digital transformation, digital financial inclusion, and financial literacy, while there are many other variables not examined in this study that affect the performance of MSME actors with disabilities.